Puppet for absolute beginners : hands-on - Mannambeth, Mumshad (Packt Publishing, 2019)
"Puppet is a leading IT automation platform in DevOps that is used to manage various stages of the IT infrastructure life cycle, including the provisioning, patching, configuration, and management of operating system and application components across enterprise data centers and cloud infrastructures. This course introduces a beginner to basic fundamentals of Puppet with easy to do hands-on exercises that you can practice right in the browser. The course introduces basic use cases of Puppet followed by an introduction to Puppet Setup, Architecture, Puppet Resources, Classes, Manifests, Profiles, Facts etc. Each lecture is accompanied by a set of coding exercises giving the user a hands-on experience in developing Puppet Manifest Files."--Resource description page